2010
DOI: 10.1016/j.rehab.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular and muscle-tendon system adaptations to isotonic and isokinetic eccentric exercise

Abstract: The literature tends to show that isotonic mode leads to a greater strength gain than isokinetic mode. This observation could be explained by a greater neuromuscular activation after IT training. However, the specific muscle adaptations induced by each mode remain difficult to determine due to the lack of standardized, comparative studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 120 publications
7
78
1
2
Order By: Relevance
“…These characteristics can promote both hypertrophic response and swelling of the assessed area, which could have lasted up to the post-training CSA assessment. The mean muscle hypertrophy per session (~ 0.3%) found in the present study is very similar to that found in untrained individuals after high intensity-low volume isokinetic eccentric training (~0.3%) 28 . After low intensity-high volume training modality (i.e., eccentric cycle ergometer training), LaStayo et al 29 found a 52% increase of muscle fiber cross-sectional area after 32 eccentric training sessions performed within 8 wk.…”
Section: Discussionsupporting
confidence: 88%
“…These characteristics can promote both hypertrophic response and swelling of the assessed area, which could have lasted up to the post-training CSA assessment. The mean muscle hypertrophy per session (~ 0.3%) found in the present study is very similar to that found in untrained individuals after high intensity-low volume isokinetic eccentric training (~0.3%) 28 . After low intensity-high volume training modality (i.e., eccentric cycle ergometer training), LaStayo et al 29 found a 52% increase of muscle fiber cross-sectional area after 32 eccentric training sessions performed within 8 wk.…”
Section: Discussionsupporting
confidence: 88%
“…It is well known that external torque exerted by the knee extensors in the IT mode is constant throughout the entire range of motion, whereas it increases in the IK mode from short to long muscle length. Although each mode creates a different mechanical load on the muscles, to date, the specific effects of IT and IK eccentric exercises on neuromuscular and musculoskeletal systems have not been determined probably considering the difficulties to compare eccentric contraction in similar experimental conditions (Guilhem et al 2010a). Yet, this comparison needs to standardize both modes to exclude non-controlled effects such as movement velocity, contraction duration or amount of mechanical work.…”
Section: Introductionmentioning
confidence: 99%
“…Despite different methodology of the experiments, the groups with ECC regime showed better results than the groups with traditional CON training regarding the enhancement of: jumping height (8%), movement frequency by 11% (Lindstedt, et al, 2002) The effect of eccentric training on coordination CON and ECC muscle contractions differ in the process of movement programming at the level of the central nervous system (CNS). The study by Guilhem et al (2010) has shown a higher level of EEG activity of the cortex with ECC contraction in relation to CON contraction. At muscular level, with similar power intensity a lower level of EMG activity was recorded during ECC compared to CON contraction (Biglan-Ritchie & Woods, 1976).…”
Section: The Effect Of Eccentric Training On Strength Developmentmentioning
confidence: 94%